O ensino de filosofia no colégio Manoel Ribas entre os anos 1979 e 1989: diários de classe e experiências de professoras - Fontoura, Sandra Isabel da Silva (2022)
This doctoral thesis was conducted in the Graduate Studies Program in Education at UFSM, in Research Line 2 - Public Educational Policies, Educational Practices and their Interfaces. Its general objective was to understand the constitution of the teaching of Philosophy as a subject taught at Manoel Ribas School - Santa Maria/RS, between the years of 1979 and 1989, a period that corresponds to the dictatorship and the gaps of political opening. The class diaries and the interviews with three Philosophy teachers who worked in the period were the corpus of the investigation. It was sought to understand, based on this corpus, the experiences of teaching Philosophy at school in the context of the Military Dictatorship and the beginning of the country's redemocratization process. Emerged from the hermeneutic analysis conducted the theoretical-methodological orientation adopted, in the understanding of the contents that should be taught and the ways in which they were taught in the period. Gadamer’s hermeneutic orientation (1997; 1999), in the editions of the work “Truth and Method”, articulates the understanding of history through a philosophical perspective, from which the past is conceived as practices of the lived in its possible encounters with the present. The analysis of the corpus, which was called “archives” made it possible to recover the historical memory of the teachers, based on the interviews and their class diaries from the Second and Third Years of High School. The thesis pursued throughout the investigation is expressed as follows: the archives constituted during the research, demarcated by the dark period of our history and the beginning of the democratic opening, give visibility to what was taught about Philosophy and its modes of transmission in the classroom, as political conditions in the country were slowly changing. It is, therefore, a important historical research, which can contribute significantly to the philosophical and educational community to keep the memory about the ways of Philosophy as a school subject in Brazil, in order to prevent the past from being erased and/or denied. Thereby, it is expected that the history of the subject can return as a tensioning and problematizing force of the present lived with the High School Reform (2017) and BNCC (BRASIL, 2018).